Training for the production of organic fertilizer from kitchen waste in Rukti Endah Village, Central Lampung Regency - Syaiful Bahri; Yuli Ambarwati; Notiragayu Notiragayu; Lina Marlina; Andi Setiawan (Universitas Muhammadiyah Magelang, 2022)
For the majority of farmers, the limited availability of subsidized fertilizers in Rukti Endah Village, Seputih Raman District, poses a problem because it lowers agricultural production. Academics at the University of Lampung initiated a socialization about organic fertilizer production to solve this problem. The aim of this community service is to train and educate people on how to make organic fertilizer from kitchen waste in order to overcome restrictions on fertilizer subsidies. The methods used in community service activities are lectures, demonstrations of making compost and group discussions attended by 30 participants. The activity's outcomes revealed an increase in community knowledge of the process of transforming waste into compost and liquid organic fertilizer in Rukti Endah Village (60.6%). The final products have been used to support agricultural production in Rukti Endah Village and the area around it.